New York Drug Law Evaluation Project, 1973 ([Verlag nicht ermittelbar], 1984)
This data collection contains the results of a study created in response to New York State's 1973 revision of its criminal laws relating to drug use. The Association of the Bar of the City of New York and the Drug Abuse Council jointly organized a joint committee and a research project to collect data, in a systematic fashion, (1) to ascertain the repercussions of the drug law revision, (2) to analyze, to the degree possible, why the law was revised, and (3) to identify any general principles or specific lessons that could be derived from the New York experience that could be helpful to other states as they dealt with the problem of illegal drug use and related crime. This data collection contains five files from the study. Part 1 contains information gathered in a survey investigating the effects of the 1973 predicate felony provisions on crime committed by repeat offenders. Data include sex, age at first arrest, county and year of sampled felony conviction, subsequent arrests up to December 1976, time between arrests, time incarcerated between arrests, and number and type of short-span arrests and incarcerations. Part 2 contains data gathered in a survey meant to estimate the number and proportion of felony crimes attributable to narcotics users in Manhattan. Case records for male defendants, aged 16 and older, who were arraigned on at least one felony charge in Manhattan's Criminal Court, in 1972 and 1975, were sampled. Data include original and reduced charges and penal code numbers, and indicators of first, second, third, and fourth drug status. Part 3 contains data gathered in a survey designed to estimate the number and proportion of felony crimes attributable to narcotics users in Manhattan. Case records for male defendants, aged 16 and older, who were arraigned on at least one felony charge in Manhattan's Criminal Court or Manhattan's Supreme Court, were sampled from 1971 through 1975. Eighty percent of the sample was drawn from the Criminal Court while the remaining 20 percent was taken from the Supreme Court. Data include date of arraignment, age, number of charges, penal code numbers for first six charges, bail information (e.g., if it was set, amount, and date bail made), disposition and sentence, indications of first through fourth drug status, first through third drug of abuse, and treatment status of defendant. Part 4 contains data gathered in a survey that determined the extent of knowledge of the 1973 drug law among ex-drug users in drug treatment programs, and to discover any changes in their behavior in response to the new law. Interviews were administered to non-randomly selected volunteers from three modalities: residential drug-free, ambulatory methadone maintenance, and the detoxification unit of the New York City House of Detention for Men. Data include sources of knowledge of drug laws (e.g., from media, subway posters, police, friends, dealers, and treatment programs), average length of sentence for various drug convictions, maximum sentence for such crimes, the pre-1974 sentence for such crimes, type of plea bargaining done, and respondent's opinion of the effects of the new law on police activity, the street, conviction rates, and drug use. Part 5 contains data from a survey that estimated the number and proportion of felony crimes attributable to narcotics users in Manhattan. Detained males aged 16 and older in Manhattan pre-trial detention centers who faced at least one current felony charge were sampled. Data include date of admission and discharge, drug status and charges, penal code numbers for first through sixth charge, bail information, and drug status and treatment.